Studies on the control effect of Bacillus subtilis on wheat powdery mildew. Issue 10 (20th May 2021) - Xie, Deshan; Cai, Xuewei; Yang, Chunping; Xie, Linjun; Qin, Guangwei; Zhang, Min; Huang, Yong; Gong, Guoshu; Chang, Xiaoli; Chen, Huabao
Abstract: BACKGROUND: Wheat powdery mildew is a worldwide fungal disease and one of the main diseases harming wheat production. Bacillus subtilis is a vital biocontrol bacteria with broad‐spectrum antimicrobial activity. In this study, we systematically studied the control effect of B. subtilis on wheat powdery mildew. RESULTS: The control efficiency of 4 × 10 5 CFU ml −1 B. subtilis on wheat leaves was 71.75% in vitro and 70.31% in a pot experiment. Application of 4 × 10 5 CFU ml −1 B. subtilis significantly inhibited spore germination (spore germination rate of 22.23%) and increased appressorium deformity (appressorium deformity rate of 69.33%). This was significantly different from the results in the sterile water treatment. Through transcriptome sequencing analysis, we found that differentially expressed genes were mainly enriched in the biosynthesis and metabolism of amino acids (including phenylalanine), carbon metabolism, the pentose phosphate pathway and other pathways. In particular, the plant hormone signal pathway gene nonexpressor of pathogenesis‐related genes 1 ( NPR1 ) was significantly upregulated. CONCLUSION: B. subtilis at concentrations of 4 × 10 5 CFU ml −1 had a significant control effect on wheat powdery mildew and can inhibit germination of the conidial germ tubes and the normal development of appressorium. B. subtilis may induce disease resistance in wheat to control wheat powdery mildew, and this effect is related to the salicylic acid‐dependent signal pathway. © 2021 Society of Chemical Industry. Abstract : Bacillus subtilis had a significant control effect on wheat powdery mildew and may induce disease resistance which is closely related to the salicylic acid‐dependent signal transduction pathway.